MONSTER AVENGER - Owen, David; Ermos, George (London : Usborne Publishing Ltd., 2023)
"The sea creatures near Haven Bay are acting very strangely, attacking boats, and Alex senses some dark power is controlling them. When he tracks down his friend the water dragon, he finds it's been infected too. If he can't find a way to stop it, the deadly parasite it's carrying could spread throughout the seas.After battling storms, electric eels and an army of angry crabs, Alex realises that the only way he and his team can save the dragon and all their ocean friends is by going inside the dragon...gulp!" -- Publisher's description
Keywords: Neptune, Alex (Fictitious character) -- Juvenile fiction; Children's stories, English; Dragons -- Juvenile fiction; Monsters -- Juvenile fiction; Marine animals -- Juvenile fiction; Fantasy fiction